Regaining Control Citizens who follow politicians on social media and their perceptions of journalism. Issue 2 (7th February 2019) - Fisher, Caroline; Culloty, Eileen; Lee, Jee Young; Park, Sora
Abstract : The use of social media by politicians has received much scholarly interest. However, much less is known about the citizens who follow them and whether their motivation to seek information directly from political actors is linked to perceptions of journalism practice. To address this gap, this paper examines the motivations of news users, in six countries (Australia, Germany, Ireland, Spain, UK and USA), who also follow politicians and political parties on social media. Analysis of data from the Reuters Institute Digital News Report 2017 shows the desire to access information unfiltered by journalists was the primary motivation, followed by partisan support, and dissatisfaction with elements of mainstream political reporting. Additional logistic regression analyses for each country reveals these 'followers' are younger, have a higher interest in political news, stronger political orientation and efficacy, and participate more in sharing and commenting, than 'non-followers'. Drawing on contemporary gatekeeping theory and the curation of information flows, this paper highlights the desire of these politically interested news users for greater control over the information they consume and raises questions about the impact of negative perceptions of journalism on the desire to seek alternative information sources.